Good and Bad Tongues: Iconographic Clarifications of Talking Signs (I) - Sigüenza Martín, Raquel (Eikón / Imago, 2014)
The tongue, as the organ of speech, offers us two aspects: if it is properly used it becomes an instrument for praise and goodness, but, when it is perfidiously handled, it can cause disasters. This article is a study about its ambivalence and, especially about the sins of the tongue, its iconographic representation and how blasphemers, liars or flatterers were punished. Its positive aspects will be studied in a next article.